2004
DOI: 10.1038/sj.sc.3101591
|View full text |Cite
|
Sign up to set email alerts
|

Spinal subdural haematoma: how relevant is the INR?

Abstract: Study design: Case report. Objective: To report a rare cause of spinal cord compression. Setting: University Hospital, Wales, UK. Case report: A 67-year-old gentleman on oral anticoagulation for atrial fibrillation presented with a 4-h history of progressive loss of sensation and weakness in both legs; there was no history of trauma. On examination, he had a flaccid paraplegia with altered sensation in the L1,2,3 dermatomes and complete anaesthesia in the L4,5 distribution. Knee and ankle jerk reflexes were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 7 publications
1
8
0
4
Order By: Relevance
“…2,5,9,11,14,16,17,22) In many cases, these symptoms are preceded by events such as minor trauma. However, delayed onset was also reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,9,11,14,16,17,22) In many cases, these symptoms are preceded by events such as minor trauma. However, delayed onset was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar SSH usually presents with cauda equina syndrome or lumbago. 2,5,9,11,14,16,17,22) We report a case of lumbosacral subdural hematoma with subarachnoid hemorrhage (SAH) following a dive into the sea, which manifested only as headache at the beginning and caused lumbago a few days later.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be caused by underlying abnormalities, including neoplasms, arteriovenous malformations, arachnoiditis or syringomelia. [5][6][7][8][9] sSDH is an established complication of lumbar puncture 10 and spinal anaesthesia, with the possibility of permanent disability related to these common procedures. Domenicucci et al 3 reviewed 106 published patients with non-traumatic acute sSDH and found that 54% (n = 57) of the patients were affected by deficits of homeostasis.…”
Section: Spinal Subdural Haematomamentioning
confidence: 99%
“…L'héma-tome sous-dural rachidien (HSR), accident majeur [1] et rare des AVK [2][3][4] serait dû à la diffusion d'une hémorragie à partir des espaces sous-arachnoïdiens. L'espace sous-dural n'est qu'un espace virtuel [5] d'où la rapidité d'installation des signes de compression radiculomédullaire.…”
Section: Commentairesunclassified